Small intestinal bleeding and stricture caused by Meckel's diverticulum. Issue 8 (11th August 2022) - Nakatani, Shinya; Inoki, Kazuya; Tashiro, Tomoe; Yamaguchi, Sayaka; Gocho, Toshihiko; Yanagisawa, Fumito; Konda, Kenichi; Tojo, Masayuki; Kubota, Yutaro; Katagiri, Atsushi; Yamamura, Fuyuhiko; Takeuchi, Yoshiaki; et al.
Abstract: A 44‐year‐old man presented to our hospital with lower gastrointestinal bleeding. We performed balloon‐assisted enteroscopy, which revealed diverticulum and stricture at the ileum. The patient underwent segmental small bowel resection and diagnosed with Meckel's diverticulum. We should keep in mind the possibility of intestinal stricture due to Meckel's diverticulum. Abstract : Endoscopic images obtained by balloon‐assisted enteroscopy showing (A) the diverticulum (arrow) and the intestinal stricture (arrowhead) near the diverticulum (B). Small bowel series during BAE showing the diverticulum (arrow) and small intestine beyond the stricture (arrowhead).